On the Composition and Function of the Carbohydrate Moiety of Tissue-Type Plasminogen Activator from Human Melanoma Cells - Rijken, D C; Emeis, J J; Gerwig, G J (Thrombosis and Haemostasis, 1985)
Two variants (I and II) of tissue-type plasminogen activator (t-PA) from human melanoma cells were separated by Lysine Sepharose chromatography. The carbohydrate compositions of the forms were determined by gas-liquid chromatography. Variant I contained 12.8 g and variant II 7.1 g of carbohydrate per 100 g protein. Both variants contained N-acetylgalactosamine, suggesting O-glycosylation in addition to N-glycosylation. The possible role of N-linked oligosaccharides for the biological activity of t-PA was studied using t-PA secreted by melanoma cells in the presence of tunicamycin, an inhibitor of N-glycosylation. The latter t-PA showed the same plasminogen activating and fibrin binding properties as normally glycosylated t-PA, indicating that N-linked carbohydrate is not involved in the fibrinolytic activity of t-PA.
Keywords: Plasminogen activator; Tissue plasminogen activator; Tissue; type plasminogen activator; Fibrinolysis; Carbohydrates; Tunicamycin